2019
DOI: 10.4103/ijd.ijd_724_16
|View full text |Cite
|
Sign up to set email alerts
|

The association of metabolic syndrome and insulin resistance in early-onset androgenetic alopecia in males: A case–control study

Abstract: Background:Men with premature androgenetic alopecia (AGA) are found to be susceptible to cardiovascular diseases, metabolic syndrome (MS), diabetes mellitus and hypertension, and also premature baldness can have a definite negative impact on self-image and self-esteem in these patients. The aim of this study was to assess the strength of association between MS and/or insulin resistance (IR) in males with early-onset AGA.Methods:A total of 50 male patients with premature AGA and equal number of age-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
1
17
3
2
Order By: Relevance
“…In our examination, we found that there were factually critical contrast among patients and controls in BMI, which concurred with the investigation done by [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our examination, we found that there were factually critical contrast among patients and controls in BMI, which concurred with the investigation done by [18].…”
Section: Discussionsupporting
confidence: 91%
“…Androgenetic alopecia in male creating before multi year old enough with at any rate Grade III of Hamilton-Norwood grouping is named as beginning stage or untimely AGA. Men with untimely AGA are seen as vulnerable to cardiovascular maladies, metabolic disorder (MS), diabetes mellitus, hypertension, and furthermore untimely hair loss can have a positive negative effect on the mental self view and confidence in these patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…2 Some studies have claimed that androgenetic alopecia may be associated with hypertension, metabolic syndrome, central obesity and other cardiovascular risk factors. [3][4][5][6][7] For example, it has been shown that body mass index (BMI) of male patients with androgenetic alopecia may be higher than BMI of healthy controls and higher BMI might be correlated with lower level of zinc in hair, which in turn, may have a role in the pathogenesis of androgenetic alopecia. 8 There are other studies that show that moderate or severe androgenetic alopecia may be associated with the combination of high BMI and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…In age-matched control subjects, the correlation between age and hyperuricemia was consistent with that previously reported. 18 Swaroop et al 19 IR has been shown to increase the risk of AGA. 10,11,21 Higher UA levels probably precede IR, 22…”
Section: Discussionmentioning
confidence: 99%
“…Swaroop et al 19 and Matilainen et al 20 showed a significant relationship between insulin resistance (IR) and early‐onset AGA. However, further pathophysiological mechanisms are still unclear.…”
Section: Discussionmentioning
confidence: 99%